Political party negotiations, income distribution, and endogenous growth - Roberto Chang (Federal Reserve Bank of Atlanta, 1995)
This paper examines the determination of the rate of growth in an economy in which two political parties, each representing a different social class, negotiate the magnitude and allocation of taxes. Taxes may increase growth if they finance public services but reduce growth when used to redistribute income between classes. The different social classes have different preferences about growth and redistribution. The resulting conflict is resolved through the tax negotiations between the political parties. I use the model to obtain empirical predictions and policy lessons about the relationship between economic growth and income inequality. The model is consistent with the observation that differences in growth rates across countries are negatively related to income inequality. However, government policy cannot simultaneously increase growth and reduce inequality.
Keywords: 330; Economic policy; Income distribution; Political science